Role of Foreign Institutional Investment in Indian Derivatives Market - Gautam, Arun Kant; Sharma, Priyanka (Indian Journal of Finance, 2009)
FIIs are allowed to invest in equity derivatives as per SEBI guidelines. FIIs were inactive during the whole of 2002 and for the first 5 months of 2003 also. The equity markets were during this phase passing through a dull phase. Once the markets started moving up smartly, FII action has emerged in the derivatives markets along with an increasing exposure in the cash market itself. Reflecting the congenial investment climate, the total number of FIIs registered with SEBI increased to 882 as on March 31, 2006 compared to 685 a year ago, an increase of 197 over the year.The National Stock Exchange of India, the world’s most active market for single stock futures, continued to see very rapid growth.